System Relations in the Vocabulary of the Russian Language (Global Scientific Review, 2022)
The article deals with the systemic relations of the Russian language, their role and interrelation. It is impossible to analyze lexical units separately; they must be considered in relation to each other. Systemic lexical relations include paradigmatic (level), syntagmatic (linear) and derivational